1979
DOI: 10.1111/j.1365-2621.1979.tb09143.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Polygalacturonase Softening of Cucumber Pickles by Calcium Chloride

Abstract: Cucumbers were fermented and held for 30 days in equilibrated solutions containing low NaCl (11-13" salometer) and high NaCl (18.5-20.5" salometer) with and without CaCl, and/or polygalacturonase (PG). CaCl, and PG treatments did not interfere with fermentation. Separately, CaCl, enhanced firmness of pickles while PG was effective in causing excessive softening. When CaCl, was present in PG containing solutions, softening by PG was inhibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 8 publications
6
31
0
1
Order By: Relevance
“…On average, PG activity levels were low in both brining processes and further decreased in samples after desalting and finished product processing. Furthermore, the levels of calcium in the two processes should be sufficient to prevent enzymatic tissue softening at these low PG activities [29,30], which is congruent with the lack of correlation between PG activity and firmness values observed.…”
Section: Texture Qualitysupporting
confidence: 53%
“…On average, PG activity levels were low in both brining processes and further decreased in samples after desalting and finished product processing. Furthermore, the levels of calcium in the two processes should be sufficient to prevent enzymatic tissue softening at these low PG activities [29,30], which is congruent with the lack of correlation between PG activity and firmness values observed.…”
Section: Texture Qualitysupporting
confidence: 53%
“…29 As pectic substances are involved in the textural characteristics of cucumbers, PG could play a major role in texture expression. 6,7,29,33,34 In our research, PG increased significantly (P < 0.05) in all equilibrated tissues in comparison with raw (unsoaked) cucumber. The higher value of PG activity might be a response to immersion-equilibration, and this increased activity might produce tissue alteration owing to the capacity of PG for cell wall pectin hydrolysis, especially considering that only 18% (AE1%) of pectin was methylated according to measurements performed in cell walls isolated from raw cucumber mesocarp tissue.…”
Section: Enzyme Assaysmentioning
confidence: 73%
“…35 The cementing effect is primarily due to the calcium-pectate of the middle lamella. That Ca and pectins are key components in the textural performance of cucumber tissue has been well demonstrated by various researchers [6][7][8]35 in relation to the textural response of blanched or fermented cucumbers. Buescher et al 36 reported that calcium addition to the fermentation solutions reduced tissue softening produced by pectinolytic-polygalacturonase activity.…”
Section: Compression and Relaxation Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Las disminuciones de textura se atribuyen a la modificación de los constituyentes pécticos debido principalmente a la acción de enzimas pectinolíticas implicadas én el mecanismo biológico de degradación. Tanto en pepinillos como en aceitunas negras, se ha puesto de manifiesto que la adición de sales de calcio a la salmuera inicial consigue reducir significativamente las pérdidas de textura que se producen durante la fermentación (Garrido et al, 1986;Buescher et al, 1979). En el caso de los pepinillos, se continúa investigando a nivel básico para conocer precisamente el tipo de interacción entre el ion Ca** y ios polisacáridos de la pared celular que explique su efecto positivo sobre la textura (McFeeters y Fleming, 1991).…”
Section: Influencia De La Fermentación Sobre Las Características Sensunclassified